Molecular Targets of Bis (7)-Cognitin and Its Relevance in Neurological Disorders: A Systematic Review - Sánchez-Vidaña, Dalinda Isabel; Chow, Jason Ka Wing; Hu, Sheng Quan; Lau, Benson Wui Man; Han, Yi-Fan (Frontiers in Neuroscience, 2019)
Background: The exact mechanisms involved in the pathogenesis of neurodegenerative conditions are not fully known. The design of drugs that act on multiple targets represents a promising approach that should be explored for more effective clinical options for neurodegenerative disorders. B7C is s synthetic drug that has been studied for over 20 years and represents a promising multi-target drug for the treatment of neurodegenerative disorders, such as AD. Aims: The present systematic review, thus, aims at examining existing studies on the effect of B7C on different molecular targets and at discussing the relevance of B7C in neurological disorders. Methods: A list of predefined search terms was used to retrieve relevant articles from the databases of Embase, Pubmed, Scopus, and Web of Science. The selection of articles was done by two independent authors, who were considering articles concerned primarily with the evaluation of the effect of B7C on neurological disorders. Only full-text articles written in English were included; whereas, systematic reviews, meta-analyses, book chapters, conference subtracts, and computational studies were excluded. Results: A total of 2266 articles were retrieved out of which 41 articles were included in the present systematic review. The effect of B7C on molecular targets, including AChE, BChE, BACE-1, NMDA receptor, GABA receptor, NOS, and Kv4.2 potassium channels was evaluated. Moreover, the studies that were included assessed the effect of B7C on biological processes, such as apoptosis, neuritogenesis, and amyloid beta aggregation. The animal studies examined in the review focused on the effect of B7C on cognition and memory. Conclusions: The beneficial effects observed on different molecular targets and biological processes relevant to neurological conditions confirm that B7C is a promising multi-target drug with the potential to treat neurological disorders.